A Journey from Thermally Tunable Synthesis to Spectroscopy of Phenylmethanimine in Gas Phase and Solution. Issue 65 (15th October 2020) - Melli, Alessio; Potenti, Simone; Melosso, Mattia; Herbers, Sven; Spada, Lorenzo; Gualandi, Andrea; Lengsfeld, Kevin G.; Dore, Luca; Buschmann, Philipp; Cozzi, Pier Giorgio; Grabow, Jens‐Uwe; Barone, Vincenzo; et al.
Abstract: Phenylmethanimine is an aromatic imine with a twofold relevance in chemistry: organic synthesis and astrochemistry. To tackle both aspects, a multidisciplinary strategy has been exploited and a new, easily accessible synthetic approach to generate stable imine‐intermediates in the gas phase and in solution has been introduced. The combination of this formation pathway, based on the thermal decomposition of hydrobenzamide, with a state‐of‐the‐art computational characterization of phenylmethanimine laid the foundation for its first laboratory observation by means of rotational electric resonance spectroscopy. Both E and Z isomers have been accurately characterized, thus providing a reliable basis to guide future astronomical observations. A further characterization has been carried out by nuclear magnetic resonance spectroscopy, showing the feasibility of this synthetic approach in solution. The temperature dependence as well as possible mechanisms of the thermolysis process have been examined. Abstract : A multidisciplinary approach involving organic synthesis and high‐resolution molecular spectroscopy has led to the definition of a thermally tunable formation route for imines. Its application to phenylmethanimine combined with an integrated rotational spectroscopy–quantum chemistry protocol has enabled the full characterization of the latter, thus providing the means for future astronomical observations.